The impact of EMI on student English writing proficiency in a Spanish undergraduate engineering context - del Mar Sánchez-Pérez, María (Studies in Second Language Learning and Teaching, 2023)
This study analyzes the influence of English medium instruction (EMI) on student English writing development in a Spanish undergraduate context, a language skill that remains underexplored in EMI research at tertiary level. Through a longitudinal pre- and post-test method, it explores the writing progress of EMI engineering students as compared to the achievement of a group of English as a foreign language (EFL) learners, according to different quantitative and qualitative writing measures. Results show a positive impact of EMI on student writing development at the levels of lexical accuracy and vocabulary. However, other writing areas, such as syntax, grammar, organization, or fluency, appeared unaffected. These findings challenge, to some extent, the widespread assumption that EMI contributes to improving student English language proficiency. This study suggests that sole exposure to the language in EMI contexts does not suffice to improve students’ English writing abilities beyond the area of vocabulary. Therefore, it argues for the inclusion of language skill support within EMI programs to provide students with opportunities to achieve a comprehensive development of their English language and writing competence.